2007
DOI: 10.17221/2026-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction caused by 450C Timber Jack wheeled skidder (Shefarood forest, northern Iran)

Abstract: ABSTRACT:In forest harvesting operations usually after using skidding machinery (skidders), traces of soil damage in the form of soil compaction and wheel and logs ruts can be seen in the forest soil. Soil bulk density, which represents soil compaction, decreases soil porosity, infiltration rate and aeration and these in turn increase runoff and water erosion in the harvested area. On the other hand, a decrease in soil aeration prevents root growth and decreases the vegetative cover. In this study the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Naghdi et al [5] in their research for two soil types (clay soil with high and low liquid limits) using 450 C Timber Jack wheel skidder showed that the effect of skidder traffic on an increase in soil bulk density at sample locations was significant. The range of soil bulk density increases in sample pits due to a different number of machinery passes was from 15.8% to 62.6% compared to the control area.…”
Section: Introductionmentioning
confidence: 99%
“…Naghdi et al [5] in their research for two soil types (clay soil with high and low liquid limits) using 450 C Timber Jack wheel skidder showed that the effect of skidder traffic on an increase in soil bulk density at sample locations was significant. The range of soil bulk density increases in sample pits due to a different number of machinery passes was from 15.8% to 62.6% compared to the control area.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the amount of soil dry bulk density in sample locations of skid trail, it was also concluded that by increasing the traffic of a skidder from 14 to 20 passes, soil bulk density changes were insignificant. Naghdi et al (2007) showed that the soil bulk density increase compared to the control caused by different rates of traffic of Timber Jack 450C skidder along skid trails was between 15.8% and 62.6%. The study that was carried out along the skid trail with clay soil showed that there was no significant difference in the soil bulk density increase between two types of soil (clay soil with high liquid limit and clay soil with low liquid limit).…”
mentioning
confidence: 96%
“…So previous research was focused on soil compaction during skidding operations in mountainous conditions in Iran while there seems to be no study to show its influence in plain areas which is considerably different from mountainous conditions (Mosaddeghi et al 2000;Naghdi et al 2007;Najafi et al 2009;Agherkakli et al 2010;Bagheri, Naghdi 2011). Moreover, few studies have focused on soil compaction caused by rubber-tired skidders such as Timber Jack 450C or farm tractor and even fewer have followed a mechanized logging operation study in plantation areas like the study by Nikooy et al (2013).…”
mentioning
confidence: 99%